Legal Protection of Famous Trademarks in Indonesia: Between National Regulation and Global Counterfeiting Challenges - Yani, Ahmad; Darmawan, Didit; Hardyansah, Rommy; Marsal, Antonino Pedro; Silva, Eugenia Brandao Da (Journal of Social Science Studies, 2023)
The phenomenon of famous trademark counterfeiting has become a significant problem in the current era of globalization. A famous trademark reflects the identity of a product or company, and becomes a symbol of reputation, quality, and consumer trust. This research aims to analyze the challenges in the legal protection of famous trademarks in the national and international scope. The research findings show that although Law Number 20 Year 2016 on Trademarks and Geographical Indications provides a legal protection for famous trademarks, the effectiveness of its implementation still faces various obstacles. One of them is the need for proof of trademark recognizability, which is often not easy to obtain in every counterfeiting case. Strengthening law enforcement and increasing public awareness on the importance of respecting Intellectual Property Rights are also very important. The protection of famous trademarks is the responsibility of the government, and involves the active role of the community, business actors, and consumers. With a comprehensive approach, feasibility and fairness in the protection of famous trademarks can be realized more effectively.